Synthesis, characterization, and thermomechanical properties of liquid crystalline epoxy resin containing ketone mesogen. Issue 4 (8th September 2016) - Lin, Yi‐Sheng; Hsu, Steve Lien‐Chung; Ho, Tsung‐Han; Cheng, Shi‐Shiun; Hsiao, Yu‐Hsiang
Abstract : This study focuses on the synthesis of a novel liquid crystalline epoxy resin (LCER) based on ketone mesogenic group. The chemical structure, melting range, and liquid‐crystalline phase transition behavior of the LCER were characterized using Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, mass spectroscopy, differential scanning calorimetry (DSC), and polarized optical microscopy (POM). Two endothermal peaks and one exothermal peak appeared in the DSC curves. A birefringent liquid crystalline texture was observed with POM during heating. The curing reaction of the LCER was monitored by DSC using diaminodipheylmethane (DDM) and diaminodiphenylsulfone (DDS) as curing agents, respectively. The results showed that the curing reaction of LCER/DDM proceeded faster than that of LCER/DDS in the initial stage. Birefringence was observed with POM during the curing processes. The results of thermomechanical properties showed that the glass transition temperatures of the cured LCERs were higher than 230°C, and that the LCER crosslinked networks were thermally stable up to 360°C. The LCER crosslinked networks showed much higher glass transition temperature, storage modulus, and thermal conductivity, and a lower coefficient of thermal expansion both in the glassy region and the rubbery region compared to those of a common epoxy resin (diglycidyl ether of bisphenol A). POLYM. ENG. SCI., 57:424–431, 2017. © 2016 Society of Plastics Engineers